English and other languages in a plurilingual pedagogical approach: A case study from northern Italy - Irsara, Martina (Glottodidactica, 2023)
Language teaching constantly needs to be adapted to changing societal realities, such as the spread of English as an international language or the growing linguistic complexity in Europe. A key question is whether and how languages could be treated together in school programmes to cater to a multilingual milieu. This article analyses a plurilingual pedagogical approach that is adopted in a few primary schools in the Italian province of South Tyrol. The research is a qualitative case study and draws on various theoretical perspectives, including the method model developed by Richards and Rodgers (1982, 2001, 2014). The dataset comprises analogue and digital data gathered through participant observation, field notes, personal communications, audio recordings, and school documents. Results show how a multilingual turn has taken root in the context examined, while reinforcing English acquisition.